The Headmaster Leadership Style on Junior High School: A Qualitative Analysis - handayani suhelmi; GistituatiNurhizrah Nurhizrah; yahya yahya (Jurnal Aplikasi IPTEK Indonesia, 2019)
The purpose of this research is to describe the leadership style of Junior High School. This research focused on the leadership style of the headmaster, communication with the teachers, employees and the improved teachers’ performance. This research was conducted at Junior High School and used qualitative data collection method with one headmaster of junior high school and 10 teachers. This research used observation, interview and documentation study. The result shows that the headmaster of Junior High School had done the leadership duty very well; by used democratic and transformational style, and authoritarian if needed. The subject always tried to improve teachers’ maximum performance, communicated efficiently and interactively. Then, there are some major role in the school’s improvement and achievements, either academic or non academic. It became the proof that there is a relationship between maximum teacher performance and student achievement at Junior High School. From this research results, there were suggested that headmaster need to maintain and improve the school’s quality.